STUDI TENTANG MINAT BELAJAR PESERTA DIKLAT PADA MATA DIKLAT GOOGLE FORM DI BALAI DIKLAT KEAGAMAAN BANJARMASIN TAHUN 2019 - Abdul Hamid (WIDYABORNEO, 2021)
The purpose of this study was to determine the learning interest of the training participants of the Google Form training course by Balai Diklat Keagamaan Banjarmasin. The subjects of this study were participants of Substantive Technical Training for Multimedia-Based Learning Media in 2019 with 30 respondents. Data collection is done through questionnaires and observations. The data collected is qualitative data with the processing carried out qualitatively which is to do a qualitative descriptive analysis with a percentage. The results obtained in this study are that the learning interest of the training participants with each indicator of feeling happy, attention, relevance, and involvement of the training participants is very good.